EME's Organisational Transformation - Safei, Su'aidi (2012)
"Today should be better than yesterday and tomorrow must be better than today", is the right phrase to motivate oneself to have the ambition to progress and advance. Environment changes require organisations to take strategic steps that organisations can continue to develop properly in accordance with the changes that occur.